The applicability of 'voice of the customer' tools to an indigenous organisation in a developing country : a thesis submitted to Massey University in partial fulfilment for the degree of Masters in Philosophy (Quality Systems), Massey University of Manawatu, Palmerston North, New Zealand - Lewis, Janice Ann (Massey University, 2012)
The value and applicability of western management theories and practices to the developing world is rarely discussed within the current rush to globalise the world economies, capture untapped wealth and seek to establish businesses within indigenous societies. This is especially relevant to the use of Voice of the Customer (VOC) methods and tools when applied to indigenous peoples and service organisations, where customer information is used to design or improve services. There has been limited concentration and much debate as to whether VOC tools are as effective as anticipated, and can solve the unique problems that appear when used in unfamiliar diverse cultures in developing countries. A risk when using a particular method or management technique is the desire and expectation that it will be transferable for use in similar businesses in other countries. Service quality is reliant on what the customer feels and often cannot be measured easily. This can be compounded in a developing nation scenario, by the fact that methods are usually developed, implemented, interpreted and validated through a western ‘lens’. Armstrong and Pont et al (2011, page 6 -7) describe these issues succinctly when they state… ‘a survey of the leading academic journals suggest that well over 90% of the articles published are concerned with establishing basic causality behind certain phenomena. Very few studies investigate whether a certain method used by management is effective or not …. as practitioners we are more interested in what works than the intricacies of causality’. This research specifically explored the use of VOC tools in the Bougainville Village Court (VC) to identify service elements customers considered important to the functioning of the VC in their village communities. Tools that were used included quantitative measurement tools - a combined Garvin–SERVQUAL tool, the RATER model, and Quality Function Deployment (QFD) principles, and the more qualitative New Zealand Business Excellence Criteria (NZBEC). The research demonstrated that the quantitative VOC methods used did not fully fit, or account for some service elements important to the customer in this particular context, where societal trust and continuous contact are important service elements. The methods used were thus, unable to completely capture the full humanistic elements and contributing causal factors. In this research study cultural context in the form of history, environment, tradition, community relationships and structures, played a vital role in determining what the customer considered were important service elements. It was found that these elements were more easily captured through use of the more qualitative NZBEC as it enabled collection of more diverse perspectives through its open question structure. Generic VOC ‘western developed’ quantitative tools did gather VOC information. However, they were only effective after adaptation to each VC location and after cultural input. Cultural analysis from indigenous people to interpret the data is recommended as a prerequisite and standard part of VOC methodology in a developing country scenario. This research suggests assessment and analysis based solely on ‘western’ VOC methods and statistics will not capture the VOC fully and could lead to misinterpretation or fail to acknowledge the real voice of the customer and the causal and contextual factors contributing to customer responses.
Keywords: Customer service; Management; Total quality management; Administration of criminal justice; Social life and customs; Bougainville Island; Papua New Guinea